Analisis Prosedur Audit Kepatuhan Belanja pada Universitas ABC oleh Kap Kanaka Puradiredja, Suhartono Cabang Surabaya - Yuliawati, Ira Sukma; Suryaningrum, Diah Hari (IAI Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the shopping compliance test procedures at ABC University implemented by the Kanaka Puradiredja Public Accounting Office, Suhartono Surabaya Branch. The research method used is descriptive qualitative with a case study approach and the technical data analysis used is descriptive analysis which is used to describe the shopping compliance test procedures implemented by KAP Kanaka. The shopping compliance audit procedure at ABC University is carried out by asking clients for data, then doing sampling, asking clients for data, vouching, and confirming if things are found that are not clear. The test results relating to the expenditure compliance test carried out by KAP Kanaka show that ABC University has fulfilled material matters, both internal control compliance and compliance with legislation. In terms of value and transactions, there were no differences in recording, so it can be ensured that transactions have been presented accurately.